Articulatory Suppression Impairs Working Memory for Ostensibly Unvocalizable Abstract Sounds. Issue 1 (3rd April 2018) - Nees, Michael; Leong, Peri
ABSTRACT: Both subvocal articulatory rehearsal and attentional refreshing have been advanced as rehearsal mechanisms for verbal material (including speech sounds) in working memory, but the mechanism of rehearsal for nonverbal sounds – especially timbral attributes of sounds – remains unclear. Since timbral attributes of sounds often have been assumed to be unvocalizable, researchers have suggested that working memory for timbre must involve an attentional or sensory (rather than subvocal) maintenance mechanism. Two experiments examined the role of subvocal rehearsal and attentional refreshing in working memory for timbre using sounds that were designed to be abstract, unvocalizable, and devoid of apparent mnemonic semantic connections. Participants heard either three (Experiment 1) or two (Experiment 2) brief (250 ms), abstract sounds. Following an 8000 ms retention interval, participants heard a single probe sound and indicated whether the probe had been a member of the original set. During the retention interval, manipulations were introduced to suppress subvocal articulatory rehearsal, attentional refreshing, or both. Across both experiments, all conditions with articulatory suppression during the retention interval showed worse memory performance than a control condition. Effects of attentional refreshing suppression were inconsistent. These experiments suggested that subvocal imitation may be an important mechanism of rehearsal in working memory for timbre – a finding that presents complications for existing theoretical perspectives on both verbal and nonverbal working memory.